2009
DOI: 10.1523/jneurosci.2769-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Characterization of Human Fetal Brain Development with Diffusion Tensor Magnetic Resonance Imaging

Abstract: The human brain is extraordinarily complex, and yet its origin is a simple tubular structure. Characterizing its anatomy at different stages of human fetal brain development not only aids in understanding this highly ordered process but also provides clues to detecting abnormalities caused by genetic or environmental factors. During the second trimester of human fetal development, neural structures in the brain undergo significant morphological changes. Diffusion tensor imaging (DTI), a novel method of magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
343
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(371 citation statements)
references
References 41 publications
26
343
2
Order By: Relevance
“…If we were to use an anatomical marker as an example, then diffusion sensor magnetic resonance imaging has shown that the cortical and subplate in humans thickens in the second trimester of human fetal development. 41 However, this occurs later at E14-18 in the fetal mouse gestational period. 42 Again, this raises the importance of larger animal studies, in particular non-human primates, to provide a more representative model.…”
Section: Un-injected Thresholding Intensitymentioning
confidence: 98%
“…If we were to use an anatomical marker as an example, then diffusion sensor magnetic resonance imaging has shown that the cortical and subplate in humans thickens in the second trimester of human fetal development. 41 However, this occurs later at E14-18 in the fetal mouse gestational period. 42 Again, this raises the importance of larger animal studies, in particular non-human primates, to provide a more representative model.…”
Section: Un-injected Thresholding Intensitymentioning
confidence: 98%
“…During the waiting period, which lasts approximately four weeks, afferents receive instructive input and start projecting onto their cortical targets. Concurrently, the corpus callosum extends in an anterior to posterior fashion (Huang et al, 2009(Huang et al, , 2006, first synapsing on neurons in the transient subplate zone before establishing its definitive connections in the cortical plate (Kostovic and Jovanov-Milosevic, 2006;Volpe, 2009). Once thalamocortical connections are established, which has been noted to occur between 24-32 PCW (Figure 2), sensory stimuli including visual and auditory input can reach the developing cortex (Kostovic and Jovanov-Milosevic, 2006).…”
Section: Midfetal Periodmentioning
confidence: 99%
“…Early afferent fibers appear from as early as 8-10 PCW forming the cerebral stalk at the level of the thalamus . High field DWI studies have demonstrated the emergence of projection-and commissural fibers, including the internal capsule and corpus callosum from as early as 13 and 15 PCW respectively (Huang et al, 2009;Takahashi et al, 2012) (Figure 2). …”
Section: Embryonic and Early Fetal Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior commissure (AC) can be clearly identified in DTI color-encoded map (see, e.g., Huang et al 2009) and was aligned with the upper edge of the rectum in the single-subject template at 20 weeks. Population-averaged FA maps and DTI color-encoded maps at 20 weeks were generated with affine (Woods et al 1998) and LDDMM transformation.…”
Section: Establishment Of Population-averaged Dti Mapsmentioning
confidence: 99%